Effect of anti‐browning agents and package atmosphere on the quality and sensory of fresh‐cut Birgit and Lady Claire potato during storage at different temperatures. Issue 4 (13th February 2020) - Dite Hunjek, Draženka; Repajić, Maja; Ščetar, Mario; Karlović, Sven; Vahčić, Nada; Ježek, Damir; Galić, Kata; Levaj, Branka
Abstract: The influence of cultivar, anti‐browning agents, package atmosphere, storage time and temperature on quality, and sensory of fresh‐cut potatoes (FCP) were investigated. Slices of cv. Birgit and Lady Claire were dipped in water, sodium chloride solution (1%) and sodium ascorbate solution (2%) and stored under air, vacuum, and active modified atmosphere at 3 and 10°C for 10 days. Dry matter, pH, color and texture properties, gas composition within packages, and microbial activity were monitored during storage. Also, raw and boiled FCP were sensory evaluated. Examined influences significantly affected majority of FCP properties. Generally, sodium ascorbate showed more efficiency in browning prevention, as well as vacuum‐packaged samples were more acceptable. Storage at 3°C did not have significantly better effect compared to storage at 10°C. FCP quality and sensory retained well till the 8th day of storage. Cv. Birgit demonstrated greater potential for FCP production. Practical applications: Although fresh‐cut potato (FCP) has been extensively investigated, there is an existing need for further study of adequate cultivars, as well as prevention of enzymatic browning as important factor for maintaining its quality. This research provides a better insight of the influence of legally permitted anti‐browning agents ( quantum satis ) that are accepted by consumers as natural and nontoxic food additives, as well as low‐cost packaging method and storage conditions on FCP quality and sensory properties in order to achieve and improve its required quality and durability during storage. Furthermore, present study could also contribute to better knowledge of relatively new potato cultivars on the market.